Role of Effective Corporate Governance and Motivational Leadership in Increasing Productivity and Efficiency of Human Resources (Global Journal of Management and Business Research, 2020)
Workforce motivation is a concern for the corporate sector. Corporate governance and leaders have a significant role in motivating human resources to increase their productivity and efficiency. This study aims at identifying the impact of effective corporate governance and motivational leadership factors on the productivity and efficiency of human resources. The authors, in this paper, critically discussed determining human resources, elements of effective corporate governance, features of ideal corporate leader, and motivational leadership factors that influence the workforce in organizations. This study is descriptive and conceptual, and used secondary data obtained from different books, journals, and research articles (both theoretical and empirical) in the related field.
Keywords: corporate governance; efficiency; human resources; motivational leadership; motivational factors; productivity